Autonomic behavioral impairment induced by simazine exposure during early life of male mouse is mediated by Lmx1a/Wnt1 pathway. Issue 4 (22nd December 2021) - Li, Xueting; Hu, Xiaomeng; Jiang, Yujia; Wang, Dandan; Wang, Ting; Li, Baixiang
Abstract: Simazine is a widely used herbicide and known as an environmental estrogen. Multiple studies have proved simazine can induced the degeneration of dopaminergic neuron resulting in a degenerative disease‐like syndrome. Herein, we explored the neurotoxicity of simazine on the dopaminergic nervous system of embryos and weaned offspring during the maternal gestation period or the maternal gestation and lactation periods. We found that simazine disturbed the crucial components expression involved in Lmx1a/Wnt1 pathway of dopaminergic neuron in embryonic and weaned offspring. Furthermore, morphological and behavioral tests performed on weaned male offspring treated by simazine suggested that the grip strength, autonomic exploring, and the space sense ability were weakened, as well as the pathological damage of dopaminergic neuron was clearly observed. But, the same neurotoxicity of simazine is less significantly observed in female offspring. Our findings will provide reliable reference for the determination of environmental limits and new insight into the pathogenesis of nonfamilial neurodegenerative diseases related to environmental risk factors.